Successful Outcome of a Heterotopic Pregnancy: A Case Report - Begum, Hamida; Tesfaye, Muluken; Ashrafi, Fatima (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Heterotopic pregnancy refers to the presence of simultaneous pregnancies at two different implantation sites. We present an unusual case of term heterotopic pregnancy, the ectopic pregnancy being abdominal implantation. The co-existence of spontaneous full term intra-uterine with advanced abdominal ectopic pregnancy and both viable babies without any residual effect or congenital anomalies is one of the rarest forms of heterotopic pregnancy. Other than Ultrasound, increased HCG, or alpha feto protein, sophisticated modern technology like MRI or CT’s Scan absolutely needed for proper diagnosis, placental localization and vascularization to prevent intra-operative catastrophies. J Bangladesh Coll Phys Surg 2023; 41(4): 338-341